Wahlmöglichkeiten und Wettbewerb in der Krankenversorgung : Steuerungsinstrumente in Deutschland, den Niederlanden, der Schweiz und den USA im Rechtsvergleich (Studien aus dem Max-Planck-Institut für Ausländisches und Internationales Sozialrecht, 2010)
This volume sheds light on the structures and causal relationships of normative control through competition in a particularly cost-intensive area of ​​medical care: the hospital sector. The Federal Republic of Germany, the Netherlands, Switzerland and the USA are the focus of the study, which compares law and is supplemented by economic comments. In all countries, competition serves as a control instrument to achieve welfare state allocation effects and counteract cost increases. However, the understanding of competition as well as the type and scope of competitive elements and the control mechanisms intended for them vary considerably. At the same time, competition is itself subject to normative control. It is in a tense relationship with state intervention and regulation, which are committed to solidarity and needs-based care and which characterize conventional statutory security systems. In detail, the study deals with different aspects and consequences of the use of competitive elements to achieve goals, with the further development of institutional and organizational structures, with the qualification of competition as a structural principle of health law and, as a result, finally with the solidifying developments towards "health competition law" and control.